New species and records of the genus Amphichroum Kraatz, 1857 from the Himalayan Region and Tibet (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2021)
Taxonomic and faunistic data for seven species of the genus Amphichroum Kraatz, 1857 (Omaliinae) from the Himalayan Region and Tibet are provided. All species are (re-)described and illustrated, including two new species: A. ahrensi sp. n. from India (West Bengal) and A. telnovi sp. n. from western Nepal. A new combination is proposed for A. nepalicum (Coiffait, 1982) comb. n., originally described in the genus Arpedium Erichson, 1839. The lectotype is designated for A. anthobioides Champion, 1925. Distributional distributional maps for all covered species are provided. Amphichroum monticola Cameron, 1928 is recorded from Nepal for the first time.